Management Curriculum Through the Semester Credit System (SKS) In the Competency Standards To Improve the Quality of Education - Sasmito Pribadi; Mujamil Qomar; Agus Zaenul Fitri (Publisher Cv. Inara, 2022)
Credit semester system in SMAN 1 Kedungwaru Tulungagung and MAN 1 Trenggalek based on the results of the interview with the head of school/madrasah which states that to provide services to students who have learning speed is high, the policy of the ministry of education that should pay attention to the potential of each student, the school/madrasah already accredited A reserves the right to determine the implementation is better that the package system and the credit system semester, as well as pay attention to the readiness of the school. The purpose of this study was to determine the planning, implementation and supervision of the Semester Credit System (SKS) in the competency standards to improve the quality of education at SMAN 1 Kedungwaru Tulungagung and MAN 1 Trenggalek. This research is useful to add insight, mindset, attitude, and experience as an effort to explore the implementation of the curriculum through the semester credit system in improving the quality of education. The research approach using qualitative methods. The technique of data collection was participant observation, in-depth interviews and documentation. The data analysis technique used is 1) the data analysis of a single case, 2) the analysis of cross-site. The research results show that: the Planning competency standards done with meet the criteria graduation graduation criteria subjects and each semester and education unit in the meeting of the board the teacher set. The implementation of the competency standards do with the criteria for graduation students in accordance with the provisions applicable in the madrasah. Supervision competency standards of graduates conducted on each end of the semester include the presence of students, educators, until the results of the evaluation.